PELATIHAN PEMBUATAN BIOAKTIVATOR PUPUK ORGANIK CAIR DARI LIMBAH KEJU (Whey) DI DESA SUMBEREJO KOTA BATU - Hudha, Mohammad Istnaeny; D., Rini Kartika; A., Dwi Ana; Minah, Faidliyah Nilna; Jimmy, Jimmy (Dharma: Jurnal Pengabdian Masyarakat, 2022)
Sumberejo Village is located at the foot of Bukit Banyak and north of the Among Tani City Hall, which consists of three hamlets, namely Dusun Krajan, Dusun Sumbersari and Dusun Sumberejo. Sumberejo village has potential in agriculture. To accommodate the activities of the farmers, the “Barokah” Farmers Group was formed. The development of technology and fertilizers used in agriculture is increasing so that the use of chemical fertilizers is increasingly difficult to avoid. Over time, this will have a serious impact, especially on soil nutrients. In addition, things that need attention are agricultural waste in the form of vegetables and cheese waste (whey) generated from the activities of the cheese-making industry. Cheese waste (whey) is generally thrown away in rivers and can cause an unpleasant aroma, but it will also trigger the growth of disease-causing microorganisms. The objectives to be achieved from this training activity for the manufacture of natural bioactivators are to utilize vegetable waste and whey as an alternative source of microbes in the manufacture of bioactivators and to provide information on public knowledge about the manufacture of liquid organic fertilizer from agricultural waste using independently produced bioactivators. this activity is to present the material and then carry out direct practice to make natural bioactivators. Then an evaluation of the products produced and the processes carried out by the training participants is carried out.